Emergent Use of a Branched Arch Device to Treat an Ascending Aortic Rupture: A Branch-to-Branch Through-and-Through Wire Technique to Compensate for Rotation Error. (August 2019) - Eleshra, Ahmed S.; Kölbel, Tilo; Rohlffs, Fiona; Scheerbaum, Martin; Konstantinou, Nikolaos; Tsilimparis, Nikolaos
Purpose: To present a novel means of overcoming a rotation error when treating a ruptured ascending aorta with a branched arch endograft.Technique: The technique is demonstrated in an 83-year-old patient with cardiac and respiratory comorbidities and a contained rupture of the ascending aorta who was referred for endovascular therapy. Computed tomography angiography (CTA) showed progressive pseudoaneurysm and mediastinal hematoma, but the limited landing zone required the use of an inner branched arch endograft that was designed for another patient. The device became malrotated clockwise during deployment, so cannulation of the first inner branch was done using a branch-to-branch through-and-through wire from the second inner branch. The final angiogram showed a good result, with patency of the supra-aortic vessels and exclusion of the rupture. The patient was discharged 2 weeks later without complications. The 1-month CTA was free from endoleak. The patient returned to his normal activity 3 months later.Conclusion: The use of a branched arch stent-graft for emergent repair of a ruptured ascending aorta is feasible.